Study protocol of the BLANKET trial: a cluster randomised controlled trial on the (cost-) effectiveness of a primary care intervention for fear of cancer recurrence in cancer survivors - Niek J de Wit; Charles W Helsper; Yvonne L Luigjes-Huizer; Marije L van der Lee (BMJ Open)
Introduction Many successfully treated patients with cancer suffer from fear of cancer recurrence (FCR), affecting their quality of life and their physical, emotional, cognitive and social functioning. Effective psychological interventions for FCR exist but are not widely available, as they are typically offered by specialised psycho-oncology professionals and institutes. Concurrently, the role of primary care in cancer and survivorship care is increasing. Therefore, there could be a role for general practitioners (GPs) and mental health workers (MHWs) working in primary care in supporting patients with FCR. In the current study, the effectiveness of a primary care delivered FCR intervention will be evaluated.Methods and analysis A two-armed cluster randomised trial will be conducted. The primary outcome will be FCR severity; secondary outcomes will be FCR-related distress, healthcare uptake and healthcare costs. Primary care practices in the Netherlands will be invited to participate in the study. Participating practices will be stratified by size and socioeconomic status and randomised. In the control arm, practices will provide care as usual. In the intervention arm, practices will offer the cognitive–behavioural FCR intervention that is being studied, which consists of an intake with the GP and five sessions with the MHW. Patients who have finished successful curative treatment for cancer between 3 months and 10 years ago will be invited to participate in the study by invitation letter from their GPs. Participating patients will fill out questionnaires at baseline, after 3 months and after 12 months. Data on healthcare use will be collected from their electronic health records. Qualitative interviews are held at T1 with patients and practitioners in the intervention group.Ethics and dissemination The Medical Research Ethics Committee (METC) Utrecht has reviewed the study in accordance with the Dutch Medical Research Involving Human Subjects Act (WMO) and other applicable Dutch and European regulations. Based on the requirements of the WMO, the METC Utrecht has issued an approval of the above-mentioned study. Any protocol amendments will be communicated to all relevant parties. Written consent is obtained from study participants. Results will be dispersed through peer-reviewed publications and scientific presentations.Trial registration number NL7573 in the Netherlands Trial Register on 25-02-2019.